2021
DOI: 10.21203/rs.3.rs-343284/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of face surgical and N95 face masks on speech perception and listening effort in noise

Abstract: Daily life conversation relies on speech perception in quiet and noise. Due to the COVID-19 pandemic, the usage of face masks has become mandatory in many situations. Acoustic attenuation of sound pressure by the mask tissue reduces speech perception ability especially in noisy situations. Mask also impede the process of speech information from sight of the moving mouth (lip reading). In a prospective exploratory experimental study including 17 normal hearing participants, speech perception in noise and listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Face masks have been shown to impair acoustic details of the speech signal in several studies, with N95/FFP2 masks showing quite a strong attenuation in mid to high frequencies, while surgical face masks show only moderate influence on the acoustic speech signal (Caniato et al, 2021;Corey et al, 2020). Confirming this impact behaviourally, Rahne et al (2021) found impaired speech perception in noise when wearing a surgical face mask compared to no mask, while participants performed even worse when using an N95 mask. As well as reducing acoustic details, information transmitted via visual input is completely missing or severely reduced.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Face masks have been shown to impair acoustic details of the speech signal in several studies, with N95/FFP2 masks showing quite a strong attenuation in mid to high frequencies, while surgical face masks show only moderate influence on the acoustic speech signal (Caniato et al, 2021;Corey et al, 2020). Confirming this impact behaviourally, Rahne et al (2021) found impaired speech perception in noise when wearing a surgical face mask compared to no mask, while participants performed even worse when using an N95 mask. As well as reducing acoustic details, information transmitted via visual input is completely missing or severely reduced.…”
Section: Introductionmentioning
confidence: 77%
“…The adverse effect of face masks on speech comprehension has been investigated in various studies on a behavioural level (Brown et al, 2021;Giovanelli et al, 2021;Rahne et al, 2021;Toscano & Toscano, 2021;Yi et al, 2021). Despite the overall agreement of the adverse effects of face masks on speech comprehension, it has been unclear which features of speech processing are specifically affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some indication that the effect is stronger AV compared to A conditions (Figure 3), but not significantly. Previous studies showed acoustic degradations of speech features for speakers wearing a face mask (Corey et al, 2020; Rahne et al, 2021). Despite these mostly being restricted to higher frequencies, this might have an impact on listeners who have trouble hearing and need every information available to aid their speech processing (Motlagh Zadeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hadley and Ward point close attention to the physical gestures used as a substitute for verbal exchange where background noises impair vocal comprehension [75]. The normalisation of face masks worn during conversation has been shown to degrade the acoustic quality of the voice as a result of suppressing higher frequency ranges, commonly depended upon to recognise articulations of consonant sounds [76][77][78]. This poses a further disadvantage to those hard of hearing [79] as well as non-native speakers, often more dependent on reading the face [80,81].…”
Section: Non-verbal Contingencies and Face Coveringsmentioning
confidence: 99%